A novel statistical apportioning method for lanthanides among host phases in rock and soil samples. (December 2022) - Vodyanitskii, Yuriy; Minkina, Tatiana; Rajput, Vishnu D.
Abstract: Lanthanides (Ln) are considered a type of heavy metals. To analyze Ln host phases in the rock and soil, the sequential extraction method is frequently applied. However, the notable shortcoming of the sequential fractionation method is the insufficiently high selectivity of the reagents used and incomplete dissolution of target phases. As a result, a significant part of the host phase is retained in the residue with an unknown composition. Therefore, in the current study, a novel statistical apportioning method for Ln among host phases was developed, taking into account the chemically homogeneous Ln-bearing phases. For this purpose, the statistical analysis is used to determine the Ln content in X phases in the rock and soil based on the analysis of the regression equation of the total content, Ln = f (Xphase ). The reliability criterion of the dependence Ln = f (Xphase ) is the correlation coefficient ' r '. This new method is efficient in the case of Ln enrichment of rock and soil when the Ln content is >40% of the Clarke value (i.e., crustal abundance) and r > r crit . The lower layers of the soil profile are dominated by accessory minerals, and the total P content there reflects the presence of monazite and apatite; the Ti content, the presence of titanite (titanosilicate). The proposed statistical method based on total element analysis provides a significant share of Ti- and P-bearing host phases, which is inaccessible through the dissolution method. Thus, it is concluded that the proposed method is a valuable addition for Ln's extraction for identification of Ln host phases in soils and in rocks. Highlights: Novel statistical apportioning method is developed to analyze homogeneous Ln-bearing phases. This method provides a significant share of the Ti bearing phases and P bearing phases. It is significant for Ln's extraction for identification of Ln host phases in soils and in rocks.